Syringic acid from rice roots inhibits soil nitrification and N2O emission under red and paddy soils but not a calcareous soil - Yufang Lu; Yufang Lu; Yao Hua; Na Lv; Weijun Zu; Herbert J. Kronzucker; Herbert J. Kronzucker; Gangqiang Dong; Weiming Shi; Weiming Shi (Frontiers in Plant Science, 2022)
Syringic acid (SA) is a novel biological nitrification inhibitor (BNIs) discovered in rice root exudates with significant inhibition of Nitrosomonas strains. However, the inhibitory effect of SA on nitrification and nitrous oxide (N2O) emissions in different soils and the environmental factors controlling the degree of inhibition have not been studied. Using 14-day microcosm incubation, we investigated the effects of different concentrations of SA on nitrification activity, abundance of ammonia-oxidizing microorganisms, and N2O emissions in three typical agricultural soils. The nitrification inhibitory efficacy of SA was strongest in acidic red soil, followed by weakly acidic paddy soil, with no significant effect in an alkaline calcareous soil. Potential nitrification activity (PNA) were also greatly reduced by SA additions in paddy and red soil. Pearson correlation analysis showed that the inhibitory efficacy of SA might be negatively correlated with soil pH and positively correlated with clay percentage. SA treatments significantly reduced N2O emissions by 69.1-79.3% from paddy soil and by 40.8%-46.4% from red soil, respectively, but no effect was recorded in the calcareous soil. SA addition possessed dual inhibition of both ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) abundance in paddy and red soil. Structural equation modelling revealed that soil ammonium (NH4+) and dissolved organic carbon content (DOC) were the key variables explaining AOA and AOB abundance and subsequent N2O emissions. Our results support the potential for the use of the BNI SA in mitigating N2O emissions and enhancing N utilization in red and paddy soils.